Importância das informações contábeis nas unidades de negócio: estudo exploratório em uma empresa de Jaraguá do Sul - Bruch, Ilario (2005)
This study has the purpose to analyze the importance of precise and limpid accounting information available to strategic business unities in the taking administrative decisions process. While the business unities are, theoretically, in a minor or a large way, autonomous, when it refers to the management of profits, disbursements and investments, is indispensable that their managers and executives have access to accurate and detailed accounting information, with an accessible and suitable language according to their reality. The business unities can use these accounting information s to do a better performance s valuation of their activities. The actual global economical structure claims from the managers a higher agility in the taking decisions process more and more accurate and efficient, which request, from the data s suppliers, to elaborate information s and reports, a higher accurate and rapidity to generate these data. Frequents accounting reports, distorted and sub-utilized, available only for a few employees, or highly refined with a hard comprehension, don t shows any utility to the today s companies. We describe, at the present work, the implementation of a system unit management system of a company located at the Brazilian city of Jaraguá do Sul, Santa Catarina, that avail of the process to realize a scission, that dive the organization in to distinct ones. These don t represent significant alteration in its operations. The implementation of business strategic units management system had place in 1999 and, after four years, at January 2003, the scission divided peacefully two of the five units with more relevant alterations regarding to contractual and belonging to the society questions. With the company divided into unities, the Corporative started to act in center activities; like human resources and accountabilities; leaving the specific operations, like sales and strategic, as a executive job. This provision feasible the performance evaluation of the units in a individual way or in a general way in the corporation, allowing each unit to have a real vision of their results and responsibilities in the presence of their internal and external clients, besides the possibility of a personal attending to them